ANALISIS FAKTOR YANG MEMPENGARUHI STATUS KESEHATAN PEKERJA PEMBANGUNAN MAL PELAYANAN PUBLIK (MPP) PT SAMEROT TRI PUTRA DI MANADO - Winny Vionita Rambitan; Billy Kepel; Aaltje Manampiring (Stikes Syedza Saintika Padang, 2021)
Workers with prime health determine the level of work productivity. When the worker’s health condition are declining and eventually became ill, the ability to think and doing tasks in workplace will also declining. The purpose of this research, is to find what factors that effecting the health status dan to understand which factor has the most influence to the worker’s of the development of public service mall (PSM) of PT Samerot Tri Putra in Manado health condition. There are 40 respondets. The research activity starts by signing the agreement paper, filling in the questioneaire, measuring body weight, height, and measuring the pulse. The research method are using quantitative data, in form of analytical surveys with Cross sectional approach. Data analysis are using univariat analitic, bivariat analitic with the Chi-square tests, dan multivariat with the regretion logistic analysis. The chi square test results of each independent variables are found with the p value of nutrition status (p=0,505) and health service accsess (p=0,005). The test result of logistic regression shows that variable with the high OR which is physical working load (OR=10,102). The conclusion of this research is, the variable that has the most effect to the health is the physical and mental working load and the health service accsess . The variable that has no effect in health status is the nutrition status. The company can consider to provide expert of K3 and health clinic as the form of Company’s primary health service to deal with the worker health’s needs.Keywords: Nutrition status, working load, health service accsess, health status.